A novel active packaging material based on starch-halloysite nanocomposites incorporating antimicrobial peptides. (February 2017) - Meira, Stela Maris Meister; Zehetmeyer, Gislene; Werner, Júlia Orlandini; Brandelli, Adriano
Abstract: Corn starch was used as a polymeric matrix for development of new antimicrobial packaging prepared by casting method and using nisin or pediocin for food preservation. Halloysite clay was selected as nanofiller to promote film reinforcement and a novel approach was tested using bacteriocins adsorbed on nanoclay before incorporation into film forming solutions. Active films against Listeria monocytogenes and Clostridium perfringens were obtained, but halloysite retained antimicrobial activity when comparing to films without nanofiller addition. Results from XRD showed that the addition of bacteriocins affected the crystallinity of starch matrix, whereas SEM images showed that peptides provoked surface irregularities. Adsorption approach proved to be a promise strategy to maintain a certain crystallinity and homogeneous morphology of films and consequently influencing other properties, like improving thermal performance. In the case of nanocomposite with nisin, adsorption procedure also improved water barrier properties. Increased mechanical resistance of films containing halloysite was observed. Elongation at break (EB) increased significantly for samples with nisin or pediocin, and those containing nisin plus halloysite. Physical interactions between additives and starch matrix via hydrogen bonding were evidenced by FTIR. Color parameters L*, a* and b* were close to those obtained for control films, although higher b* values were observed for pediocin samples. These results indicate the potential of such antimicrobial nanocomposite films as food packaging material. Graphical abstract: Highlights: Starch nanocomposite films were prepared with nisin, pediocin and halloysite. Structural, mechanical and thermal properties of the films were determined. Nanocomposite films showed antimicrobial activity against food pathogens. These nanocomposites are suitable active films for food packaging.